실시간 감시를 통한 교통신호제어기의 열화 감지 - 김은영; 장중순; 오봉식; 박상철 (신뢰성 응용연구, 2018)
Purpose: A traffic signal controller needs to control and coordinate to ensure that traffic and pedestrians move as smoothly as possible. Since a traffic signal controller has a significant impact on the safety of vehicles and pedestrians, it is important to monitor the failure and deterioration of the traffic signal controller. The purpose of this paper is to propose an IoT (Internet of Things)- based monitoring system for a traffic signal controller. Methods: Every traffic signal controller has a nominal system trajectory specified when it is deployed. The proposed IoT-based monitoring system collects the system trajectory information through real-time monitoring. By comparing the nominal system trajectory and the monitored system trajectory, we are able to detect the failure and deterioration of the traffic signal controller. Conclusion: The proposed IoT-based monitoring system can contribute to the safety of vehicles and pedestrians by maximizing the availability of a traffic signal controller.
Keywords: IoT-Based Monitoring System; Traffic Signal Controller; Trajectory Comparison